The Art of Crafting Music Score Approval Plans: An Ongoing Process. Issue 4 (1st October 2016) - Hooper, Lisa
ABSTRACT: Although approval plans have long been an accepted tool for monographic collection development, they have seen comparatively slow adoption for music scores. This slow adoption is mirrored by a relative dearth of literature about music score approval plans. At a time when changes in the financial and publishing landscape are having a profound impact on collection development practices and current trends in organizational restructuring are placing greater demands on librarians' time, the need for contemporary discussion of approval plans is that much greater. This article discusses the ups and downs of one library's foray into music score approval plans.